Multivariate analysis of nutritional attributes associated with bitter pit in ’Gala’ apples - Amarante, Cassandro Vidal Talamini do; Chaves, Daniela Vieira; Ernani, Paulo Roberto (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to identify nutritional attributes, assessed in the flesh and skin tissues, that provide a better discrimination regarding bitter pit severity in ’Gala’ apples. After four months in regular cold storage (0–1°C; 90–95% RH), fruits were segregated into four lots with different levels of bitter pit severity: null (none pit per fruit), low (1–2 pits per fruit), moderate (3–4 pits per fruit), and high (5–13 pits per fruit). Nutritional analysis (Ca, Mg, K and N) in the skin and in the flesh tissues were performed on twelve individual fruits of each severity level. The univariate analysis showed that fruits with bitter pit symptoms had lower concentration of Ca in the skin and flesh tissues, a higher concentration of K in the skin tissue, and higher values for K/Ca, Mg/Ca, N/Ca, (K+Mg)/Ca, and (K+Mg+N)/Ca ratios in the skin and flesh tissues than fruits without bitter pit. However, the canonical discriminant analysis (multivaried analysis) showed that, out of all nutritional attributes assessed in the skin and flesh tissues, K/Ca ratio in the skin provides the best discrimination between fruit with bitter pit and fruit without the disorder, followed by Mg/Ca and N/Ca ratio in the flesh tissue.